The effect of LHRHa with and without dopamine antagonist on reproductive performance in lambari Astyanax altiparanae - Roza de Abreu, Mariana [UNESP]; de Jesus Silva, Laíza Maria [UNESP]; Figueiredo-Ariki, Daniel Guimarães [UNESP]; Sato, Rafael Tomoda [UNESP]; Kuradomi, Rafael Yutaka [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Elsevier, 2022)
The present study evaluated the effect of luteinizing hormone-releasing hormone analogue (LHRHa) with and without dopamine antagonist (i.e., domperidone (D)) on the reproductive performance of lambari females (Astyanax altiparanae) as well as on secretion of 17α-20β-dihydroxy-4-pregnen-3-one (17,20β-P) and prostaglandin F2α (PGF2α)) and on the histological evaluation of ovarian structures in two independent and consecutive experiments. In the first experiment (Exp. 1), five LHRHa doses (20, 60, 180, 540, and 1620 μg/kg BW) were tested with three replicates each, while in the second experiment (Exp. 2) the dose of 180 μg/kg was tested in combination with D at a dose of 20 mg/kg with four replicates. The replicates in both experiments consisted of an experimental unit in which five females and 10 males were placed. In both experiments, two control groups were formed, 0.9% saline (negative control) and 6 mg/kg of carp pituitary homogenate (CPH), and females from all groups received the total dose in two injections (i.e., one comprising 10% of the total dose and a second one 12 h later comprising the resolving dose). There was a decrease in fertilization and hatching rates that coincided with the two highest doses of LHRHa (540 and 1620 μg/kg), suggesting that these doses may have caused hormonal overstimulation affecting egg quality. Taken together, these results were not in favor of an obvious dopaminergic control of final oocyte maturation (FOM) in lambari, since the use of LHRHa associated with D did not improve reproductive performance of lambari compared to LHRHa alone, CPH, and negative control. Plasma levels of 17,20β-P were related to FOM and/or ovulation in most cases. There was not a clear association between ovulation and PGF2α plasma levels. The CPH-treated group was the only one performing better than the negative control, increasing the spawning rate and spawning volume per female body mass as well as triggered FOM in almost all females submitted to hormonal induction, indicating that CPH is the most suitable hormonal therapy to induce FOM and ovulation in lambari (among the treatments tested here).
Keywords: Fish reproduction; Neotropical fish; Prostaglandin; Steroids